HELPFULNESS OF THREE MONTHS STRECHING ACTIVITY TRAINING PROGRAMME ON FLEXIBILITY OF HOUSEKEEPING FEMALE - Magdum, Sushant Tanaji (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study was undertaken to study and compare the effect of Three months stretching activity training programme on flexibility 60 Housekeeping females on different homes of Kolhapur (Maharashtra.) were taken as the subjects for this study. The subjects were further assigned into experimental group (N=30) and control group (N=30). Three months stretching activity training program for flexibility was given to female of experimental group only. Pre-test and post-test was conducted to measure the flexibility through sit and reach test. The age of the subjects ranged between 25-45 years. To find out the significance of difference between pre and post-test means scores of the group, mean, SD and ‘t’ test were computed and significance level was set at .01 level.. In overall statistical analysis, it was found that there was significant difference in flexibility component of as physical fitness in experimental group and Control group.